Fine-root dynamics, soil moisture and soil carbon content in a Eucalyptus globulus plantation under different irrigation and fertilization regimes - Fabião, António (2009)
The minirhizotron technique was used to study the temporal dynamics of fine-roots over a 10 month period in a Eucalyptus plantation in central Portugal.Four treatments were applied:a control without irrigation or fertilisation( C), fertilisation twice per year (F), irrigated without fertilisation( I), and irrigated and fertilised once each week with fertiliser in the irrigation water (IL). In I and IL a drip-tube system was used,and fertiliser rates were adjusted based on the estimated plant nutrient demand. Soil moisture content was measured during the same period at 5 cm depth intervals down to 90 cm depth.Soil carbon content was measured at planting,30 months after planting and54 months after planting.Interrelations between fine-root dynamics, soil moisture , and soil carbon content are discussed.